2012
DOI: 10.1080/10426914.2012.700144
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Welding Speed in High Speed Laser-TIG Welding of Magnesium Alloy

Abstract: In order to investigate the effect of welding speed on microstructures and mechanical properties in high speed welding, low power laser-tungsten inert gas (laser-TIG) hybrid welding process is proposed on AZ61 magnesium alloy. Defect-free welds are produced by employing welding speed ranging from 2,000 mm/min to 6,000 mm/min. It is found that welding speed has a significant influence on microstructures and mechanical properties of the joints. Results indicate that with rapid increasing of welding speed, both t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The efficiency of welded joints for thin plates is directly improved by increasing welding speed [102] Hybrid welding of laser-tungsten inert gas (TIG) is a new technique for high speed welding [145]. In previous research, fusion welding methods such as arc welding and low power laser beam welding were used, but the welding speed was slow [149][150][151].…”
Section: Laser-tungsten Inert Gas (Laser-tig) Hybrid Weldingmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficiency of welded joints for thin plates is directly improved by increasing welding speed [102] Hybrid welding of laser-tungsten inert gas (TIG) is a new technique for high speed welding [145]. In previous research, fusion welding methods such as arc welding and low power laser beam welding were used, but the welding speed was slow [149][150][151].…”
Section: Laser-tungsten Inert Gas (Laser-tig) Hybrid Weldingmentioning
confidence: 99%
“…Most welding rates, however, were below 2000 mm/min [152]. By increasing the welding speed from 2000 to 6,000 mm/min, Li et al [145] sought to examine the impact of welding rates on the microstructure and mechanical characteristics of high-speed welding through hybrid welding of AZ61 Magnesium alloy with laser-TIG technique. With the optimum welding speed of approximately 6000 mm/min, faulty free welds were achieved.…”
Section: Laser-tungsten Inert Gas (Laser-tig) Hybrid Weldingmentioning
confidence: 99%
“…In view of the above defects, it is of great significance to find a new welding method to improve the welding quality. Liu et al [4] concluded that increasing the proportion of He could shrink the arc by adjusting the ratio of Ar to He, and the best-welded joint was formed when the ratio was 1:1. He et al [5] proved that the weld pore rate was effectively reduced by adjusting the ratio of Ar and He in aluminium laser-MIG.…”
Section: Introductionmentioning
confidence: 99%
“…In order to accurately control the dissolution of base metals into the molten pool, a laser was introduced and formed a laser-TIG hybrid heat source. This heat source possesses better stability of the arc and higher energy density [ 28 , 29 , 30 ], which shows possibilities in Mg–Al dissimilar welding.…”
Section: Introductionmentioning
confidence: 99%